Development of a metric for assessing the competitiveness of Ukraine according to the progress of the digital transformation of the economy - N. M. Levchenko (Економічний вісник Державного вищого навчального закладу Український державний хіміко-технологічний університет, 2023)
Ukraine’s prioritization of entry into the European digital market as a foreign policy direction highlights the urgency of incorporating the global digital economy and society index (DESI) into the national statistical monitoring system. The article asserts that DESI introduction is a pressing issue. It was emphasized that although Ukraine has declared its integration into the EU's single digital market, the country is not currently participating in any international rating to assess the competitiveness of its digitalization progress. This is due to the absence of any strategic or conceptual documents that support the use of indices of the country's digital evolution. By not implementing new and improved tools for measuring digitalization as a factor of economic growth, Ukraine is severely limited in reflecting the use and impact of digital technologies, such as AI, data analytics, IoT, 3D print, automation and robots, Cloud, 5G mobile broadband, and blockchain, on the aggregate value added of different economic sectors. Currently, only the metric for determining the Digital Transformation Index of Ukraine's regions has been approved in Ukraine at the official level. However, this metric does not meet the requirements of Eurostat and therefore cannot be utilized for international comparison. It is imperative that the global Digital Economy and Society Index (DESI) metric is implemented in Ukraine's domestic practice. The constituent elements of DESI, which include connectivity, human capital, use of internet services, integration of digital technology, and digital public services, must be taken into consideration. Accordingly, an assessment was conducted to determine Ukraine's readiness for the implementation of DESI. It is justified that Ukraine's participation in the formation and presentation of information about the DESI index will allow not only to have an objective assessment of the country's place in global trends, but also to have extremely important information for international investors regarding Ukraine's confirmation of commitment to the principles of openness and transparency assumed by international obligations to enter the single digital market by harmonizing its statistical system with EU standards and practices.